Hepatitis C Virus Infection: Molecular Pathways to Insulin resistance - Parvaiz, Fahed (BioMed Central, 2011)
Chronic Hepatitis C virus has the potential of inducing insulin resistance and type 2 Diabetes Mellitus in vitro as well as in vivo . Structural and non-structural proteins of HCV modulate cellular gene expression in such a way that insulin signaling is hampered, concomitantly leads toward diabetes mellitus. A number of mechanisms have been proposed in regard to the HCV induced insulin resistance involving the upregulation of Inflammatory cytokine TNF-α, hypophosphorylation of IRS-1 and IRS-2, phosphorylation of Akt, up-regulation of gluconeogenic genes, accumulation of lipids and targeting lipid storage organelles. This review provides an insight of molecular mechanisms by which HCV structural and non-structural proteins can induce insulin resistance.